(untitled) (PerCursos, 2022)
Geodiversity is understood as the variety of rocks, minerals, fossils, landforms and physical processes that act on these abiotic elements. The recognition of aesthetic, cultural, scientific and educational values, among others, makes it possible to inventory geodiversity and conserve the portion that has significant value, in addition to favoring geotourism activities. Therefore, the present work aims to identify the waterfalls of the municipalities of Pelotas and Arroio do Padre, in Rio Grande do Sul (Brazil), with the help of collaborative cartography, in order to subsidize the proposition of geotourism itineraries for dissemination of these elements of geodiversity. Two stages of application of online questionnaires were carried out to obtain information from collaborative cartography about the occurrence and location of waterfalls in the area under study. The results obtained allowed the identification of 21 waterfalls in Pelotas and Arroio do Padre, five of which are widely recognized and cited by collaborators: Cachoeira Imigrante, Cachoeira Arco-Íris, Cachoeira Paraíso, Cachoeira Camboatá and Pousada do Moinho. It is noteworthy that collaborative cartography reinforced the knowledge of local populations and enabled the development of a cartographic product based on the understanding that individuals have. The contributions brought by them are loaded with values and understanding of their environment, with emphasis on the abiotic elements, which validate the waterfalls as a local and regional geoheritage.